Basic experimental unit size and optimum plot size for forage turnip - Cargnelutti Filho, Alberto; Storck, Lindolfo; Lúcio, Alessandro Dal’Col; Toebe, Marcos; Alves, Bruna Mendonça (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine the effect of the basic experimental unit size (BEU) on the optimum plot size estimation for the evaluation of forage turnip (Raphanus sativus) fresh matter weight. Data from fresh matter weight of 3,456 BEUs of 0.5×0.5 m (0.25 m2) were used, and 36 BEU plans, with sizes from 0.25 to 16 m2, were formed. For each BEU plan, the optimum plot size was determined by the method of maximum curvature of the coefficient of variation model. The least significant difference was calculated by Tukey’s test in 2,016 scenarios formed by the combinations of 36 optimum plot sizes (one for each BEU plan), i treatments (i = 5, 10, 15, and 20), and r replicates (r = 3, 4, 5, 6, 10, 15, and 20), considering both the completely randomized designs and the complete block ones. Optimum plot size depends on the size of the basic experimental unit. In uniformity trials with forage turnip, the evaluation of fresh matter weight should be done in basic experimental units with the smallest possible size.